2009
DOI: 10.1002/cjoc.200990050
|View full text |Cite
|
Sign up to set email alerts
|

Peroxo Complexes of Molybdenum(VI) Containing Mannich Base Ligands

Abstract: The molybdenum(VI)-peroxo complexes containing Mannich base ligands having a formula as [MoO(O 2 [where L-L=morpholinobenzyl benzamide (MBB), piperidinobenzyl benzamide (PBB), morpholinobenzyl urea (MBU), piperidinobenzyl urea (PBU), morpholinobenzyl thiourea (MBTU), piperdinobenzyl thiourea (PBTU)] have been synthesized and characterized by physico-chemical, electrochemical techniques and TGA/DTA studies. The complexes have been prepared by stirring ammonium molybdate and excess of 30% aqueous-H 2 O 2 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Evidence to support the involvement of the amine nitrogen atom is the lowering by ~ 22 -124 cm -1 the stretching frequency of the bond (C-N) in the Mannich base at 1149 cm -1 . This led to the appearance of broad bands for νC-N in all the metal complexes and most noticeable in the case of 2; this further suggests bonding of the N-atom to the central metal [25,26]. Complex 3 seemed to be a big beneficiary of complexation owing to the strengthening of its νC-O and least reduction in the νC-N. https://doi.org /10.37358/Rev.Chim.1949 Rev.…”
Section: Properties Of the Complexesmentioning
confidence: 99%
“…Evidence to support the involvement of the amine nitrogen atom is the lowering by ~ 22 -124 cm -1 the stretching frequency of the bond (C-N) in the Mannich base at 1149 cm -1 . This led to the appearance of broad bands for νC-N in all the metal complexes and most noticeable in the case of 2; this further suggests bonding of the N-atom to the central metal [25,26]. Complex 3 seemed to be a big beneficiary of complexation owing to the strengthening of its νC-O and least reduction in the νC-N. https://doi.org /10.37358/Rev.Chim.1949 Rev.…”
Section: Properties Of the Complexesmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] They are widely used in stoichiometric as well as catalytic oxidation in organic and biochemistry, 11 for example, in the oxidation of thioanisole, 12,13 methylbenzenes, 14 tertiary amines, alkenes, alcohols, 15,16 bromide 17 and also in olefin epoxidations. [18][19][20][21][22] There has been a continuous upsurge in interest in peroxo compounds of vanadium since it has been demonstrated that vanadate and peroxovanadates are capable of inhibiting the hydrolysis of phosphoproteins [23][24][25][26] and exhibit insulin-like properties.…”
Section: Introductionmentioning
confidence: 99%